Case report: Onyx embolization of tentorial dural arteriovenous fistula via the meningohypophyseal trunk and medial tentorial artery of Bernasconi-Cassinari - Hou, Kun; Yu, Jinlu (Frontiers in Neurology, 2022)
For tentorial dural arteriovenous fistula (TDAVF), the meningohypophyseal trunk (MHT) and medial tentorial artery (MTA) of Bernasconi-Cassinari are rarely used as transarterial paths to perform successful endovascular treatment (EVT). We reported a TDAVF mainly fed by the MHT. Onyx-18 casting in the MTA of Bernasconi-Cassinari under the assistance of coil embolization in proximal MHT was performed. The technique was reported in case 1. At the same time, case 2 with a similar TDAVF was chosen as a control. In case 1, a 52-year-old man suffered cerebellar hemorrhage. A TDAVF was confirmed by computed tomography angiography and digital subtraction angiography. The feeding arteries included the MHT, middle meningeal artery (MMA) and the artery of Wollschlaeger and Wollschlaeger of the superior cerebellar artery. The MHT and MTA of Bernasconi-Cassinari were hypertrophied. First, a Marathon microcatheter was placed in the MTA to wait for Onyx casting, and then an Echelon-10 microcatheter was placed in the proximal MHT trunk with an aneurysmal dilation to perform coiling to prevent Onyx reflux. Then, Onyx casting obliterated the TDAVF. Case 2 was a 75-year-old woman with TDAVF, and the MTA of Bernasconi-Cassinari was the main feeder. First, the TDAVF experienced incomplete EVT with Onyx casting via the MTA under no assistance of coil embolization in the proximal MTA. The second EVT had to be performed via MMA. Then, Onyx casting obliterated the TDAVF. Therefore, for selected TDAVFs with hypertrophied MHT, under the assistance of coil embolization in proximal MHT, Onyx casting via MHT can finish the complete EVT.